Role of fundus fluorescein angiography in macular disorders (International Journal of Biomedical Research, 2014)
Objectives: To assess and evaluate the role of fluorescein angiography as an important tool in diagnosis of macular disorders. Methods: A hospital-based prospective randomized study was done which included 50 patients who attended the OPD during study period. Detailed history was taken from the patient and a thorough ocular and systemic examination was done. All patients were examined by conventional methods of ophthalmoscopy (direct, indirect and slit lamp examination with +90 D lens) followed by a fluorescein angiography. Patients were advised necessary ocular and systemic treatment. Results : 50 cases were analyzed and sub-divided into 5 categories of AMD, Diabetic maculopathy, vascular occlusive disorders, macular dystrophy and CSCR. FFA altered the diagnosis in 40%cases and categorized the lesions in all cases. 6% of patients experienced adverse reactions. On statistical analysis, using binomial test FFA proved to be a far superior diagnostic modality than clinical examination(ophthalmoscopy). Conclusions : FFA has played major role in diagnosing wet AMD, especially in diagnosing CNVM. It is a superior diagnostic modality in differentiating macular edema and macular ischemia in vascular disorders and hence guides in further management. It provides definitive diagnosis in CSCR and detects exact leakage points. It is of immense value in diagnosing new vessels, planning for further treatment.FFA has a limited role in evaluation of macular dystrophy.